Comparison of Student Learning in Challenge-based and Traditional Instruction in Biomedical Engineering - Martin, Taylor; Rivale, Stephanie D.; Diller, Kenneth R. (Annals of biomedical engineering, 2007)
This paper presents the results of a study comparing student learning in an inquiry-based and a traditional course in biotransport. Collaborating learning scientists and biomedical engineers designed and implemented an inquiry-based method of instruction that followed learning principles presented in the National Research Council report "How People Learn" (HPL). In this study, the intervention group was taught a core biomedical engineering course in biotransport following the HPL method. The control group was taught by traditional didactic lecture methods. A primary objective of the study was to identify instructional methods that facilitate the early development of adaptive expertise (AE). AE requires a combination of two types of engineering skills: subject knowledge and the ability to think innovatively in new contexts. Therefore, student learning in biotransport was measured in two dimensions: A pre and posttest measured knowledge acquisition in the domain and development of innovative problem-solving abilities. HPL and traditional students' test scores were compared. Results show that HPL and traditional students made equivalent knowledge gains, but that HPL students demonstrated significantly greater improvement in innovative thinking abilities. We discuss these results in terms of their implications for improving undergraduate engineering education.